Dynamic interpersonal therapy for moderate to severe depression: a pilot randomized controlled and feasibility trial. Issue 6 (14th April 2020) - Fonagy, Peter; Lemma, Alessandra; Target, Mary; O'Keeffe, Sally; Constantinou, Matthew P.; Ventura Wurman, Tamara; Luyten, Patrick; Allison, Elizabeth; Roth, Anthony; Cape, John; Pilling, Stephen
Abstract: Background: Improving Access to Psychological Therapies (IAPT) services treat most patients in England who present to primary care with major depression. Psychodynamic psychotherapy is one of the psychotherapies offered. Dynamic Interpersonal Therapy (DIT) is a psychodynamic and mentalization-based treatment for depression. 16 sessions are delivered over approximately 5 months. Neither DIT's effectiveness relative to low-intensity treatment (LIT), nor the feasibility of randomizing patients to psychodynamic or cognitive-behavioural treatments (CBT) in an IAPT setting has been demonstrated. Methods: 147 patients were randomized in a 3:2:1 ratio to DIT ( n = 73), LIT (control intervention; n = 54) or CBT ( n = 20) in four IAPT treatment services in a combined superiority and feasibility design. Patients meeting criteria for major depressive disorder were assessed at baseline, mid-treatment (3 months) and post-treatment (6 months) using the Hamilton Rating Scale for Depression (HRSD-17), Beck Depression Inventory-II (BDI-II) and other self-rated questionnaire measures. Patients receiving DIT were also followed up 6 months post-completion. Results: The DIT arm showed significantly lower HRSD-17 scores at the 6-month primary end-point compared with LIT ( d = 0.70). Significantly more DIT patients (51%) showed clinically significant change on the HRSD-17 compared with LIT (9%). The DIT and CBT arms showed equivalence on most outcomes. Results were similar with the BDI-II. DIT showed benefit across a range of secondary outcomes. Conclusions: DIT delivered in a primary care setting is superior to LIT and can be appropriately compared with CBT in future RCTs.